Production, characterization, and luminescent properties of Eu3+ doped yttrium niobate-tantalate films - DEMİRCİ, SELİM (SPRINGEROPEN, 2017)
Monoclinic yttrium tantalate (M'-YTaO4, M '-YTO), and two different kinds of yttrium niobium-tantalate (M '-YTa0.85Nb0.15O4 (M '-YTNO) and Eu3+ doped M '-YTa0.85Nb0.15O4 (M '-YTNO:Eu3+)) were produced by sol-gel method and grown on single crystalline Si (100) substrate by spin coating approach. Structural properties and thermal behaviours of the films were characterized by means of X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM), and thermogravimetry and differential thermal analysis (TG-DTA). Systematic Steady-state photoluminescence and lifetime measurements in a series of yttrium niobium-tantalate with varying amounts of Eu3+ were presented. The photoluminescence spectra of the films exhibited strong blue (380-400 nm) and red (614 nm) emissions upon ultraviolet excitation. Emission intensities were strongly dependent on the host lattice composition and film morphology. 1.5% Eu3+ doped films exhibited the brightest luminescence and long lifetime extending to 1.22 ms when excited at 254 nm. To the best of our knowledge, this is the first attempt in the production of M '-YTO, M '-YTNO, and M '-YTNO:Eu3+ films on single crystalline Si (100) substrate via sol-gel spin coating.
Keywords: yttrium tantalate; sol-gel; photoluminescence; lifetime; Eu doped; THIN-FILMS; PHOTOLUMINESCENCE CHARACTERISTICS; PHOSPHORS; CHEMISTRY